2015
DOI: 10.1088/2040-8978/17/10/105801
|View full text |Cite
|
Sign up to set email alerts
|

A coupling model for amplified spontaneous emission in laser resonators

Abstract: The competition between amplified spontaneous emission (ASE) and main laser in solid-state laser resonators is investigated both theoretically and experimentally. A coupled model using the spatial volume integral instead of the Monte Carlo type raytrace technique is proposed to depict ASE in the laser resonators. This model is able to evaluate all possible reflections at both the polishing surface and the diffusive side, to calculate ASE for an inhomogeneous gain distribution, and to include the spectral corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…6 The flow chart of simultaneous calculations of ASE intensity and output power of a disk laser using Eqs. ( 7)- (13). The results of these calculations are demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…6 The flow chart of simultaneous calculations of ASE intensity and output power of a disk laser using Eqs. ( 7)- (13). The results of these calculations are demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…ASE signal intensity for disk lasers can be obtained by calculating this coefficient for disk geometry. It has been shown that ASE intensity is proportional to the multiplication of the threshold gain coefficient by the diameter of the disk 13 . Slezak et al 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For highenergy laser systems, where high inversion is crucial, additional transparent, so called 'anti-ASE caps' are used to avoid trapping of the spontaneous emission within the amplifying disk. There are a number of publications on ASE in disk lasers, mostly relying on ray-tracing for the ASE and the rate equation for the laser process, for various geometries, sometimes also taking into account the temperature [50,[91][92][93][94][95][96][97][98][99].…”
Section: Nonlinear Effects and Limitationsmentioning
confidence: 99%
“…Peterson et al [17] accounts for the heating of the thin disk and a spectral power distribution by a Lorentzian spectral power distribution of amplified spontaneous emission. Scattering of amplified spontaneous emission at the cylinder jacket was investigated by Su et al [24] with a bidirectional scattering model. [25,26] focused on the non-uniform temperature distribution and Chen et al [15] shows an analysis of the spectral power distribution of amplified spontaneous emission.…”
Section: Introductionmentioning
confidence: 99%